Analyzing the relationship between self-confidence in mathematics and students' characteristics using multinomial logistic regression - Ismail, N.A.; Awang, H. (2010)
This study investigates the relationship between self-confidence and achievement among Malaysian students using multinomial logistic regression and the data are from TIMSS 2007. Although, in general, Malaysian students had low self-confidence in learning mathematics, their performance in mathematics at the international level is higher as compared to some countries with high level of self-confidence. This study also found that, besides mathematics achievement, there are four other factors that separate the level of self-confidence among Malaysian students. These factors are gender of students, students' aspiration, use of computer for school work, having teachers who want students to do their best.